2004
DOI: 10.1128/jvi.78.13.7036-7051.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of the Genome of the Neodiprion sertifer Nucleopolyhedrovirus

Abstract: The genome of the Neodiprion sertifer nucleopolyhedrovirus (NeseNPV), which infects the European pine sawfly, N. sertifer (Hymenoptera: Diprionidae), was sequenced and analyzed. The genome was 86,462 bp in size. The C؉G content of 34% was lower than that of the majority of baculoviruses. A total of 90 methionineinitiated open reading frames (ORFs) with more than 50 amino acids and minimal overlapping were found. From those, 43 ORFs were homologous to other baculovirus ORFs, and 29 of these were from the 30 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 84 publications
6
111
0
5
Order By: Relevance
“…This indicates that the phylogenetic distance between CuniNPV and lepidoperan NPVs is much greater than between lepidopteran NPVs and GVs (Table 2). Our current picture of baculovirus genome diversity was further advanced by the genome characterization of two viruses infecting hymenopteran hosts, the Neodiprion lecontei NPV (NeleNPV) and N. sertifer NPV (NeseNPV) [23,10]. These two viruses have relatively small genomes of only 82-86 kbp encoding about 90 ORFs.…”
Section: Recent Advances In Genome Analysesmentioning
confidence: 99%
“…This indicates that the phylogenetic distance between CuniNPV and lepidoperan NPVs is much greater than between lepidopteran NPVs and GVs (Table 2). Our current picture of baculovirus genome diversity was further advanced by the genome characterization of two viruses infecting hymenopteran hosts, the Neodiprion lecontei NPV (NeleNPV) and N. sertifer NPV (NeseNPV) [23,10]. These two viruses have relatively small genomes of only 82-86 kbp encoding about 90 ORFs.…”
Section: Recent Advances In Genome Analysesmentioning
confidence: 99%
“…All 126 MaviNPV ORFs have an assigned function or homologues in other baculoviruses. The 29 genes shared by all baculovirus genomes, including the dipteran and hymenopteran baculoviruses (Herniou et al, 2003;Garcia-Maruniak et al, 2004), were also found in the MaviNPV genome. The 126 predicted ORFs are encoded by 92 % of the MaviNPV genome; the rest is made up of intergenic spaces and hrs.…”
Section: Resultsmentioning
confidence: 96%
“…Based on the polyhedrin (polh) gene, NPVs are further subdivided into group I and group II (Bulach et al, 1999;Herniou et al, 2001Herniou et al, , 2003. Recent evidence shown from the comparison of 29 baculovirus genomes indicates that baculovirus phylogeny is aligned with the classification of the hosts more closely than with morphological traits (Afonso et al, 2001;Garcia-Maruniak et al, 2004;Lauzon et al, 2004;Jehle et al, 2006). An updated classification of the family Baculoviridae, which includes four generaAlphabaculovirus (lepidopteran-specific NPV), Betabaculovirus (lepidopteran-specific GV), Gammabaculovirus (hymenopteran-specific NPV) and Deltabaculovirus (dipteran-specific NPV) -was thus proposed (Lauzon et al, 2004;Jehle et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In mosquito hosts, following the primary infection of the gastric caeca and posterior midgut by ODVs, deltabaculovirus BVs also spread the infection further from cell to cell but only to these same tissues (Moser et al, 2001). Sawfly gammabaculoviruses do not appear to have a BV phenotype (Duffy et al, 2006;Garcia-Maruniak et al, 2004;Lauzon et al, 2004) and OBs are only produced in the nuclei of midgut epithelial cells (Federici, 1997).…”
Section: Classification and Origins Of Baculovirusesmentioning
confidence: 99%